A DNA barcode library for Culex mosquitoes (Diptera: Culicidae) of South America with the description of two cryptic species of subgenus Melanoconion - Stanislas Talaga; Amandine Guidez; Benoît de Thoisy; Anne Lavergne; Romuald Carinci; Pascal Gaborit; Jean Issaly; Isabelle Dusfour; Jean-Bernard Duchemin (PLoS ONE, 2025)
Among mosquitoes (Diptera: Culicidae), the genus Culex Linnaeus is one of the most diverse in the world and includes numerous known vector species of parasites and viruses to humans. Morphological identification of Culex species is notoriously difficult and relies mostly on the examination of properly dissected male genitalia which largely prevents female and immature identification during entomological, ecological or arboviral surveys. The aims of this study were (i) to establish a DNA barcode library for Culex mosquitoes of French Guiana based on the mitochondrial gene cytochrome c oxidase I (COI) marker, (ii) to compare three approaches of molecular delimitation of species to morphological identification, (iii) to test the effectiveness of the COI marker at a broader geographical scale across South America, and (iv) to discuss the internal classification of the genus Culex as regard to our phylogenetic analysis. Mosquitoes used in this study were sampled in French Guiana between 2013 and 2023. We provide 246 COI sequences for 90 morphologically identified species of Culex, including five new country records and two newly described species. Overall, congruence between morphological identification and molecular delimitations using the COI barcode was high. The Barcode of Life Data clustering approach into Barcode Index Numbers gives the best result in terms of species delimitation. Inconsistencies between morphological identification and molecular delimitation can be explained by introgression, incomplete lineage sorting, imperfect taxonomy or the effect of geographical gap in sampling. This increases by almost two-fold the number of mosquito species for which a DNA barcode is available in French Guiana, including 75% of the Culex species currently known in the territory. Finally, this study confirms the usefulness of the COI barcode in identifying Culex of South America, but also points the limits of this marker for some groups of species within the subgenera Culex and Melanoconion.